2013
DOI: 10.1088/1475-7516/2013/07/028
|View full text |Cite|
|
Sign up to set email alerts
|

Complementarity of dark matter direct detection: the role of bolometric targets

Abstract: We study how the combined observation of dark matter in various direct detection experiments can be used to determine the phenomenological properties of WIMP dark matter: mass, spin-dependent (SD) and spin-independent (SI) scattering cross section off nucleons. A convenient choice of target materials, including nuclei that couple to dark matter particles through a significantly different ratio of SD vs SI interactions, could break the degeneracies in the determination of those parameters that a single experime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 113 publications
1
36
0
Order By: Relevance
“…As we showed in Ref. 24, the combination of data from Ge and Xe leads to a substantial reduction in the contours of the reconstructed WIMP parameters. The improved energy threshold also contributes to this.…”
Section: Results For Ge and Xesupporting
confidence: 55%
See 3 more Smart Citations
“…As we showed in Ref. 24, the combination of data from Ge and Xe leads to a substantial reduction in the contours of the reconstructed WIMP parameters. The improved energy threshold also contributes to this.…”
Section: Results For Ge and Xesupporting
confidence: 55%
“…As in our previous paper, 24 we start the analysis studying the complementarity of two experiments, based, respectively on Ge and Xe. Such elements are employed by the collaborations producing the currently most stringent limits on WIMP properties and are contemplated in projects planning to extend the search to the ton scale (e.g.…”
Section: Results For Ge and Xementioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has shown that complementary target elements can break the degeneracy between the standard spindependent and spin-independent operators [32,33], and others have shown that this concept can also be applied to the larger EFT parameter space [28]. Such considerations are particularly important when incorporating the effect of interference on the event rate.…”
Section: B Comparison Of Target Elements For G2 Direct Detection Expmentioning
confidence: 99%